Developing and Evaluating an AI-Driven Arabic Listening E-Module: Integrating Intensive and Extensive Listening Through Elevenlabs - Faisal Umri; Muhbib Abdul Wahab; Maswani Maswani (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2026)
The limited availability of Arabic listening materials integrated with interactive digital technologies remains a significant challenge in enhancing listening proficiency among students in the Arabic Language Education Program at UIN Syarif Hidayatullah Jakarta. Existing resources often lack accessibility, engagement, and alignment with learning outcomes. This study aimed to develop an artificial intelligence (AI)-based Arabic listening e-module, E-sama’iy, utilizing ElevenLabs technology and structured listening activities, and to examine its effectiveness in improving students’ listening skills. Employing a Research and Development (R&D) approach based on the ADDIE model, the study was conducted through five stages: analysis, design, development, implementation, and evaluation. The feasibility of the module was assessed through expert validation, while its effectiveness was evaluated using pre-test and post-test scores of second-semester students. The findings revealed that the developed e-module was highly feasible, obtaining an average validation score of 92%. Students’ listening achievement improved substantially, with mean scores increasing from 55.4 in the pre-test to 85.9 in the post-test, accompanied by an N-Gain score of 0.68, indicating moderate-to-high improvement. Furthermore, students reported highly positive perceptions (91.88%), particularly regarding motivation, engagement, and comprehension. These findings demonstrate that E-sama’iy is an effective digital learning resource for enhancing Arabic listening skills and supporting AI-assisted language learning.